A Global Perspective on Psychologists’ and Their Organizations’ Response to a World Crisis - Gutiérrez, Germán; Barbarin, Oscar; Klicperová-Baker, Martina; Padakannaya, Prakash; Thompson, Ava; Crowe, Simon; Khoury, Brigitte (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Around the world, individual psychologists have stepped up to deliver essential services to address the social and emotional sequelae of the COVID-19 pandemic. Many psychological organizations have also responded to this public health crisis, though their efforts may be less widely recognized. Psychological organizations engaged in preventive and mitigation efforts targeted, among others, the general public, local communities, and high-risk groups such as health care providers. They disseminated mental health information to the general public, trained laypersons to provide psychological first aid, and used research to design and evaluate public health responses to the pandemic. In some countries, psychological organizations contributed to the design and implementation of public health policies and practices. The nature of these involvements changed throughout the pandemic and evolved from reactive to proactive, from local to international. Several qualities appear key to the value, impact, and success of these efforts. These include organizational agility and adaptability, the ability to overcome their political inertia and manage conflict, recognizing the need to address cultural differences, and allocating limited resources to high-risk and resource-depleted constituencies where it was needed most.